2022
DOI: 10.3390/cancers14082040
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Susceptibility and Metabolism in Fanconi Anemia

Abstract: Fanconi anemia (FA) is a rare inherited, generally autosomal recessive syndrome, but it displays X-linked or dominant negative inheritance for certain genes. FA is characterized by a deficiency in DNA damage repair that results in bone marrow failure, and in an increased risk for various epithelial tumors, most commonly squamous cell carcinomas of the head and neck (HNSCC) and of the esophagus, anogenital tract and skin. Individuals with FA exhibit increased human papilloma virus (HPV) prevalence. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 223 publications
0
1
0
Order By: Relevance
“…FANCL is a key gene involved in the FA DNA repair pathway, and its homozygous or compound heterozygous mutation can lead to the onset of Fanconi anemia (FA), which is one of the most common inherited BMFs. [3,4] FANCL is just one of the FA complementation (FANC) genes, which include a total of 22 genes, namely FANCA, FANCB, FANCC, FANCD1, FANCD2, FANCE, FANCF, FANCG, FANCI, FANCJ, FANCL, FANCM, FANCN, FANCO, FANCP, FANCQ, FANCR, FANCS, FANCT, FANCU, FANCV, and FANCW. [5][6][7] Researches have reported that heterozygous mutations in the FANC genes may lead to an increased susceptibility to tumors and acquired BMF.…”
Section: Introductionmentioning
confidence: 99%
“…FANCL is a key gene involved in the FA DNA repair pathway, and its homozygous or compound heterozygous mutation can lead to the onset of Fanconi anemia (FA), which is one of the most common inherited BMFs. [3,4] FANCL is just one of the FA complementation (FANC) genes, which include a total of 22 genes, namely FANCA, FANCB, FANCC, FANCD1, FANCD2, FANCE, FANCF, FANCG, FANCI, FANCJ, FANCL, FANCM, FANCN, FANCO, FANCP, FANCQ, FANCR, FANCS, FANCT, FANCU, FANCV, and FANCW. [5][6][7] Researches have reported that heterozygous mutations in the FANC genes may lead to an increased susceptibility to tumors and acquired BMF.…”
Section: Introductionmentioning
confidence: 99%